Preferensi Masyarakat Kab. Karo Terhadap Siaran Radio Gundaling FM Di Era Digital - Sembiring, Regina Evi Sagita Br; Rasyid, Abdul (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This research examines the preferences of the people of Karo district towards Radio Gundaling FM broadcasts in the digital era. Radio, which used to be the main source of information and entertainment, is now facing challenges from digital platforms. The results of this study found that Radio Gundaling FM still has loyal listeners, especially among 37-48 year olds who still enjoy local content such as cultural news, folk songs, and distinctive announcer interactions. However, the preferences of the younger generation aged 17-25 have shifted to digital platforms such as TikTok, Spotify, You Tube, Instagram. Radio Gundaling FM attempts to adapt by live streaming on the TikTok app and creating content for social media. This research highlights the importance of preserving local culture in radio broadcasts amidst the changing times in the digital era.